Detection of seismic anisotropy and azimuthally varying resonances from seismic data recorded at the Noto Peninsula using seismic interferometry and empirical mode decomposition - Andrés Pech-Pérez (Results in Earth Sciences)
Reducing the uncertainties in the detection of fluid-filled fractures and faults is essential for natural resource exploration and earthquake forecasting, yet it remains a complex challenge. This study explores the hypothesis that seismic anisotropy and wave resonances can help to reduce uncertainties in fracture and fault detection, particularly in the Noto Peninsula. Seismic data from KiK-net stations ISKH06 and ISKH04 are analyzed using deconvolution and empirical mode decomposition (EMD) to identify wave patterns possibly related to fluid flow and crack propagation. The ISKH06 and ISKH04 stations have boreholes equipped with triaxial accelerometers at depths of 200 m and 100 m, respectively, as well as at the surface. Deconvolution of seismic events recorded at the surface and at depth helps identify anisotropic layers. To interpret interferograms, the study utilizes a one-dimensional layered medium, empirical mode decomposition, and an orthorhombic model. Genuine resonances or tremors are identified mainly along: a) directions subparallel to horizontal stress orientations, and b) directions that traverse intersecting fractures. This study can significantly impact the fields of resource exploration and production, and earthquake preparedness, by providing strategies to mitigate the uncertainties in the detection of subsurface fractures and faults, ultimately leading to better resource management, improved characterization of fluid mobility, and enhanced seismic hazard assessments.